Structural and Symbolic Violence Exacerbates the Risks and Consequences of Sexual and Gender-Based Violence for Forced Migrant Women - Hourani, Jeanine; Block, Karen; Phillimore, Jenny; Bradby, Hannah; Ozcurumez, Saime; Goodson, Lisa; Vaughan, Cathy (Frontiers in Human Dynamics, 2021)
While much attention is focused on rape as a weapon of war, evidence shows that refugee women and girls face increased risks of sexual and gender-based violence (SGBV) both during and following forced displacement. In this paper, we argue that gendered forms of structural and symbolic violence enable and compound the harms caused by interpersonal SGBV against refugee women and girls. These forms of violence are encountered in multiple contexts, including conflict and post-conflict settings, countries of refuge, and following resettlement. This paper illustrates the consequences of resultant cumulative harms for individuals and communities, and highlights the importance of considering these multiple, intersecting harms for policy and practice.